Data vulnerability in Generation Z consumers : The role of corporate data transparency - Härkönen, Aurora (My University, 2023)
The purpose of this study was to analyse data vulnerability in Generation Z and the role of corporate data transparency regarding the phenomenon. The research question was divided into three sub-questions, which are as follows: 1. How does vulnerability occur in a data service context? 2. How does Generation Z understand data vulnerability? 3. How does corporate data transparency meet the needs of consumers experiencing data vulnerability? The research question was answered with the help of previous academic literature and empirical research. Data vulnerability was examined in light of the findings of i.e., Baker et al. (2005), Dey et al. (2020), and Palmatier and Martin (2019). Data vulnerability has similar aspects as consumer vulnerability but is experienced while using digital services. There are different ways of being data vulnerable, but the common element is giving away one’s information and not knowing exactly what is done to it and why. The role of data transparency was considered in particular in based on the findings of Acquisti et al. (2020) and Palmatier and Martin (2019). According to previous research, data transparency can be used to lessen the feeling of being data vulnerable. However, there are very few academic articles analysing this matter. There is also only little research on the representation of Generation Z in these topics, which is why Gen Z was selected as the target group for this thesis. Generation Z and its characteristics were reflected upon the findings of Seemiller and Grace (2018) and Schroth (2019), among others who consider Generation Z as determinant, diverse and digitally native group with strong moral. The theoretical framework was built by combining findings from previous research on the topic. In the empirical study, 16 qualitative semi-structured interviews were conducted. The results of the study suggest that Generation Z members feel data vulnerable to some extent. The concept was not familiar to most of them, but was associated with extensive data collection, which they could not control, and which could cause some harm to themselves. The study revealed that people from minorities in particular fear for their data especially if there would be a crisis in society that threatened them. Many are particularly concerned about their bank and health data. However, what could be interpreted based on the interviews is that state-owned companies and banks are the most trustworthy actors in the eyes of Gen Zers when it comes to data collection. The least trusted actors or companies are those of foreign origin, especially from outside Europe. The results showed that increasing corporate data transparency and facilitating control over consumers’ own data can reduce their feeling of data vulnerability. Generation Z representatives suggested a variety of ways to increase transparency and facilitate control, and many felt that these kinds of actions could increase the trustworthiness, attractiveness, and brand image of a company.

Tämän tutkimuksen tarkoituksena on tutkia datahaavoittuvuutta Z-sukupolvessa sekä yritysten dataläpinäkyvyyden vaikutusta siihen. Tutkimuskysymys jaettiin kolmeen osakysymykseen, jotka ovat: 1. Kuinka haavoittuvuus esiintyy digitaalisten palveluiden käytön yhteydessä? 2. Kuinka Z-sukupolvi ymmärtää datahaavoittuvuuden? 3. Miten yritysten dataläpinäkyvyys kohtaa datahaavoittuvien kuluttajien tarpeet? Tutkimuskysymykseen pyrittiin vastaamaan aiemman kirjallisuuden perusteella sekä empiirisen tutkimuksen avulla. Datahaavoittuvuutta tarkasteltiin etenkin Deyn ym. (2020), Bakerin ym. (2005) ja Palmatierin ja Martinin (2019) löydösten valossa. Datahaavoittuvuudella on samoja piirteitä kuin kuluttajahaavoittuvuudella, mutta datahaavoittuvuutta koetaan digitaalisten palveluiden kuluttamisen yhteydessä. Datahaavoittuvainen voi olla monella tapaa, mutta kaikkia näitä yhdistää omien tietojen luovuttaminen datapalveluiden käyttämisen yhteydessä ja epätietoisuus siitä, mitä datalla tehdään ja miksi. Dataläpinäkyvyyden merkitystä pohdittiin erityisesti Acquistin ym. (2020), Palmatierin ja Martinin (2019) tutkimusten perusteella. Aiemman tutkimuksen mukaan dataläpinäkyvyyden avulla on mahdollista vähentää yksilön datahaavoittuvuuden kokemusta. Z-sukupolven edustuksesta näiden aiheiden parissa ei ole juurikaan tutkimusta, minkä takia se valikoitui tämän tutkielman kohderyhmäksi. Z-sukupolvea tarkasteltiin muun muassa Seemillerin ja Gracen (2018) ja Schrothin (2019) löytöihin peilaten, joiden mukaan Z-sukupolvea voidaan kuvailla määrätietoisena, monipuolisena ja diginatiivina sukupolvena, jolla on vahvat arvot. Teoreettinen viitekehys rakennettiin yhdistämällä aiheeseen liittyvästä aiemmasta tutkimuksesta saatuja löydöksiä. Empiirisessä tutkimuksessa toteutettiin 16 kvalitatiivista puolistrukturoitua haastattelua. Osallistujat olivat syntyneet vuosina 1995–2005. Tutkimuksen tuloksista voidaan päätellä, että Z-sukupolven edustajat tuntevat olonsa jossakin määrin datahaavoittuvaisiksi. Termi ei ollut suurimmalle osalle tuttu, mutta se yhdistettiin laajaan datankeräämiseen, jota ei voi kontrolloida ja josta voi olla itselle jonkinnäköistä haittaa. Tutkimuksessa nousi esiin, että etenkin vähemmistöjen edustajat pelkäävät datansa puolesta, mikäli yhteiskunnassa syntyisi heitä uhkaava kriisitilanne. Monet ovat huolissaan etenkin omista pankki- ja terveystiedoistaan. Eniten luottamusta kuitenkin herättävät sellaiset tahot, jotka ovat valtio-omisteisia tai pankkeja. Z-sukupolvi kuvaili luottavansa vähiten palveluntarjoajiin, jotka ovat ulkomaisia, etenkin Euroopan ulkopuolelta tulevia. Tutkimuksesta ilmeni, että lisäämällä yritysten dataläpinäkyvyyttä ja antamalla kuluttajille lisää kontrollia omasta datasta voidaan vähentää datahaavoittuvuuden tunnetta. Z-sukupolven edustajilla oli ehdottaa erilaisia keinoja näiden lisäämiseksi ja moni koki, että sillä voisi lisätä yrityksen luotettavuutta, houkuttelevuutta sekä brändi-imagoa.
Keywords: data vulnerability, data transparency, data privacy, Generation Z, datahaavoittuvuus, dataläpinäkyvyys, datayksityisyys, Z-sukupolvi